Mainan Tradisional Di Daerah lstimewa Yogyakarta Dalam Konteks Perkembangan Kreativitas Anak - Bagus lndrayana; R.M. Soedarsono; Djoko Suryo; Timbul Haryono (Ornamen, 2010)
Every art and culture development in Indonesia always relatedwith social, politics, ecomonic and cultural, including in religious andbelieved life of the entire society. That conditions push the change anddevelopment so that was evident there is pra-Hinduism, Islam, andWestern culture. Culture product that being produced in various forms,making techniques, and philosophy that influence behavior in a holistic,including the child's play activities life. Play activities help child to createexperience, acknowledge, and skill, so that in next developmentsteps child can be brave, spontaneous, creative, imaginative, and responsive.Those activities used as a relaxation media to release stressand a/so intrinsic complex value transformation field and examinationin light have a meaningful to the formation of the child's personal. Thecomplexity of that value gives a chance to the different creativities ofchild, so that end of a toy that being made in beach environment differentwith a toy that developed in the rural place. This fact also can beseen in a toy in countryside that different from the downtown.Key Words : Toys, Transformation, Creativity